Institutional Role: Policy Bias Towards Village Development Transformation - Rahajeng, Anggi; Jaya, Wihana Kirana; Widhianta, Nanda (Universitas Diponegoro Publishing Group, Indonesia, 2026)
Decentralization has been a key element in regional development in Indonesia, with significant impacts on reducing economic and spatial disparities. While initial policies were more centered on the district/city level, the 2014 Village Law has shifted the paradigm by giving villages greater authority to manage their development. This study explores village-oriented institutional and policy changes and their impact on rural development transformation. Using a qualitative approach based on interview content and desk research, this study identifies three main themes: village authority and finance, national-regional strategic projects, and controlling agricultural land conversion. The analysis results show that pro-rural policies have increased village capacity through the Village Fund and strengthened community participation but also created dynamics of authority trade-offs with local governments. National strategic projects, especially infrastructure development, have improved connectivity and opened new economic opportunities for villages. However, major challenges remain in harmonizing spatial policies with agricultural land protection. This study concludes that pro-rural policies have accelerated sustainable rural development and promoted economic convergence between urban and rural areas. However, multi-level coordination is still needed to optimize their impact.